Civil-legal institutions in tax law enforcement. - M. Karaseva (Sentsova) (Правоприменение, 2017)
The subject. The enforcement of civil-legal institutions, such as liability for damage and unjustenrichment in tax disputes.The purpose of the paper is to identify how the civil-legal institutions may help in interpretationand enforcement of tax legal rules.The methodology. The methods of analysis and synthesis are used. The focus of the scientificanalysis concerns the decisions of the Constitutional Court of the Russian Federation,the Supreme Court of the Russian Federation and the courts of general jurisdiction.Results and scope of application. Damage (harm) caused to the state by tax arrears is fundamentallydifferent from the harm (damage) caused to the civil order, responsibility forwhich is provided by Art. 1064 of the Russian Civil Code. Concerning the damages to stateby tax arrears, these arrears don’t affect the initial assets of the state and couldn’t be reimbursedusing to the civil order (Art. 1064 of the Russian Civil Code).Concerning property deduction on personal income tax, it can't be equaled to tax (arrears)by using the legal fiction. Because the underestimation of the tax base for personal incometax leads to property losses of the budget, this situation is subject to the application of civillaw institutions.Conclusions. Today the law enforcement practice creates a situation of substitution of legalityby expediency. The essence of this situation is that, if it is not possible to solve a situationby using tax legal rules, the situations is solved by civil law, although the applicationof the civil law to these situations is not possible on the merits.